Efetivação do princípio da duração razoável do processo com a criação do Fundo de Garantia das Execuções Trabalhistas : instrumento de satisfação do jurisdicionado - Rocha, André Vitaliano de Carvalho (2013)
You need to know the problems faced by the judiciary to seek satisfactory solutions rather than palliative . This research is based on the realization of the constitutional principle of reasonable duration of proceedings in the light of the satisfaction jurisdicionado, having the guarantee fund of labor plays an instrument to realize the rights evaded justice for workers in the work by presenting possible solutions to the delay in adjudication, ensuring a fair tutelage, useful and appropriate. With the passage of time comes to increasing the number of demands in judiciary and with the advent of the Amendment n. 45, which gave the courts new powers of labor, there was the difficulty of procedural justice in the implementation of this principle of work. Thus, the lack of institutions capable of providing subsidies to effect the adjudication with the satisfaction of creating with jurisdiction over the constitutional amendment of 45 in his article 3º of the guarantee fund is intended to ensure that executions labor credits to employees evaded the workforce. Deplores the right to point out that the alien discussion on this principle and of paramount importance to provide a jurisdictional, is already well advanced with even some countries, such as Italy already collated with its legal penalty for the violation of this principle. However, the focus regarding possible solutions is based on the Guarantee Fund executions of Labor . For carrying out this research, we intend to explore a qualitative research aimed at producing knowledge for practical application addressed to solve problems. It is hoped that the deepening of this work, ensuring the company and propose mechanisms that enable an adjudication proper, fair and useful and consistent with a reasonable time, achieving the satisfaction of the courts.